2002
DOI: 10.1165/ajrcmb.26.1.4618
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Depletion and Dexamethasone Differentially Modulate Airways Hyperreactivity, Inflammation, Mucus Accumulation, and Secretion Induced by rmIL-13 or Antigen

Abstract: The intratracheal administration of interleukin (IL)-13 to hyperresponsive BP2 mice induces bronchopulmonary hyperreactivity (BHR), eosinophilia, mucus and MUC5AC accumulation, similar to those observed after ovalbumin (Ova) treatment when mice are immunized. mRNAs for IL-4 peaked at 6 h after Ova challenge, then vaned, whereas IL-13 expression was stable for a longer period, suggesting different effects. Inhalation of aerosolized methacholine by immunized mice 72-96 h after Ova reduced epithelial mucus conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 38 publications
6
72
0
Order By: Relevance
“…Glucocorticoids also suppress the expression of the arachidonic acid-liberating enzyme, cPLA, 11,14,18,38 that inhibits the production of lipid mediators, such as leukotrienes and prostaglandin. 19 This consequently leads to a decrease in the recruitment of inflammatory cells to the site of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucocorticoids also suppress the expression of the arachidonic acid-liberating enzyme, cPLA, 11,14,18,38 that inhibits the production of lipid mediators, such as leukotrienes and prostaglandin. 19 This consequently leads to a decrease in the recruitment of inflammatory cells to the site of infection.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Also, glucocorticoids inhibit immunoglobulin G (IgG), IgM, and IgA antibody synthesis, 14 phospholipase A2 enzyme (cPLA2) expression, and production of leukotrienes 15 and prostaglandins. 16 As a consequence, there is reduced neutrophil, eosinophil, and macrophage recruitment to the inflammatory site, impaired cell differentiation and survival, 8,17 decreased nitric oxide (NO) production, reduced expression of the adhesion costimulatory and major histocompatibility complex (MHC) molecules, 16,18,19 lowered pulmonary mucous secretion, 19 and impaired apoptosis. 20,21 However, glucocorticoids increase the expression of certain antiinflammatory proteins, such as lipocortin-1 and IL-10, 9 and the expression of the high-affinity receptor for leukotriene B 4 (BLT1), which increases the antiapoptotic effects of this lipid mediator.…”
Section: Introductionmentioning
confidence: 99%
“…IL-13 may act indirectly, through the activation of an l epidermal growth factor receptor cascade [7]. According to this hypothesis, SINGER et al [26] recently showed that, in mice, granulocyte depletion inhibited mucus accumulation induced by IL-13, suggesting a supportive role of these cells in mediating the effects of IL-13 on mucus. Mucus hypersecretion is believed to result, at least in part, from inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo models using transgenic mice (26) and intranasal (14) or intratracheal (27) injections of IL-13 consistently showed increased goblet cells in the airways of mice. However, one limitation of these in vivo experiments was their inability to determine the exact mechanism of how the cytokine affects mucin gene expression.…”
mentioning
confidence: 98%